Penghapusan Roya Jaminan Fidusia antara Nasabah dengan Koperasi Simpan Pinjam terhadap Hak Tanggungan atas Tanah - Sulaeman, Soeyono Arasy (Peneliti.net, 2026)
People who choose to borrow money through cooperatives to meet their funding needs. One form of business that is legally registered in Indonesia is a cooperative. Cooperatives have minor differences from other business entities such as PT, CV, Firm, or Foundation, where cooperatives are more prominent in terms of kinship and mutual cooperation to help members for the common good in accordance with the basic principles of cooperatives as regulated in Law Number 17 of 2012. Cooperatives are based on the principle of a people's economic movement rooted in mutual cooperation. They have members with an open and voluntary nature. A fiduciary ensures the transfer of ownership rights over an object based on trust, with the condition that the object of ownership rights transferred remains owned by its owner, and the fiduciary holder is required to register at the fiduciary registration office and the Mortgage Company. The termination of mortgage rights is carried out through the roya process at the National Land Agency Office. Once the mortgage object has been fully paid off, it is mandatory to obtain a certificate of ownership for the paid-off land to replace the ownership of the mortgage object.